Motivation, Satisfaction, and Retention of Sport Management Student Volunteers - James E. Johnson; Chrysostomos Giannoulakis; Nathan Felver; Lawrence W. Judge; Pierce A. David; Beau F. Scott (Journal of Applied Sports Management, 2017)
Sport management programs often partner with intercollegiate athletic departments or community sport organizations to provide student volunteers. Motivating, satisfying, and retaining the student population may constitute a challenge for academic program stakeholders. The purpose of this study was to examine the relationship between motivation, satisfaction, and retention of volunteers at undergraduate sport management programs. Three hundred and twenty-two undergraduate students from five Midwestern institutions completed a 46-item questionnaire assessing their volunteer motivation, satisfaction, and retention. Results indicated students were predominantly motivated to volunteer by Love of Sport and Career motivation factors. Career, Social, Understanding, and Enhancement motivations significantly aided in predicting satisfaction, while Career, Social, and satisfaction significantly predicted retention. Implications for sport management academic programs and directions for future research are discussed.
Keywords: Sport volunteerism; sport management students; motivation; satisfaction; retention